Intracystic Hemorrhage and Its Management During Ultrasound-Guided Percutaneous Microwave Ablation for Cystic Thyroid Nodules - Dong, Su; Sun, Lele; Xu, Jialu; Han, Zhe; Liu, Jia (Frontiers in Endocrinology, 2020)
Purpose: Intracystic hemorrhage can present occasionally during ultrasound-guided percutaneous microwave ablation (PMWA) for cystic thyroid nodules. It can affect the outcome of treatment, leading to ablation failure and even conversion to open surgery. We aim to avoid such cases in future by exploring the reasons and management of intracystic hemorrhage during ultrasound-guided percutaneous microwave ablation for cystic thyroid nodules.From March 2017 to December 2019, a total of 87 cystic thyroid nodules in 59 patients who underwent PMWA in the first hospital of Jilin university were studied retrospectively. All patients were followed at 1, 3, 6 and 12 months after treatment.Results: All patients completed the treatment successfully. 9 cystic thyroid nodules presented Intracystic hemorrhage during ultrasound-guided PMWA. The incidence of Intracystic hemorrhage is 10.3% (9/87). Larger cystic thyroid nodules were likely to Intracystic bleeding during ultrasound-guided PMWA. Intracystic hemorrhage resulted in significantly prolonged ablation time and had negative effect on the therapeutic results. All patients had no other complications. But temporary postoperative pain and local swelling were more obvious in patients with intracystic hemorrhage.Intracystic hemorrhage is not rare during ultrasound-guided PMWA for cystic thyroid nodules. Doctors should pay more attention to it, learn to deal with it and try to avoid it in clinical practice.